Integration Framework of Accounting and Auditing and its Subsequent Influence on Financial Reporting - Hussein, Firas Abdulameer; Wahhab, Asaad Mohammed Ali (Technium Social Sciences Journal, 2023)
This study aims to illustrate the profound influence that the integration and interconnection of financial accounting and auditing principles have on financial reporting and demonstrate the potential benefits of integrating financial information systems to enhance the accuracy, clarity, and usefulness of financial data. This integration is expected to contribute to more informed economic decision-making processes. A survey instrument was created consisting of three dimensions, with each dimension matching one of the research variables. The instrument was distributed to a sample population of individuals who possess expertise and practical experience in accounting and auditing. A sample size of 287 questionnaires was administered in this study. To achieve the research objectives, the study hypotheses were evaluated by conducting statistical analyses of the collected data. Furthermore, the research investigated the relationship and incorporation of the elements within the theoretical framework for global financial reporting and the principles of auditing, along with their impact on the process of financial reporting. The objective above was accomplished using several statistical methodologies, including structural equation modelling, path analysis, confirmatory factor analysis, and path derivation. In addition, longitudinal data models were developed, and regression models were estimated, incorporating autocorrelation, multiple correlations, and variance. The conceptual framework employed in the study of accounting and auditing has played a significant role in mitigating information asymmetry and promoting a greater focus on objectivity and suitability in the measuring of accounting data. The fundamental basis of this paradigm is grounded in the concepts of mixed measurement and adoption. The utilisation of historical cost and current value measures, along with the integration between the conceptual framework of accounting and the conceptual framework of auditing, play a role in promoting effective and fair financial reporting regarding the economic entity’s ability to maintain its operations in the future. Furthermore, these methods serve to guarantee an adequate level of disclosure of subsequent events, thereby reducing ambiguity.